Research on cultural landscape supported by digital technology. Issue 3 (October 2020) - Lin, Yinan; Wang, Ting; Han, Mengmeng; Liu, Siqi; Huang, ZhiLiu
Abstract: Cultural landscape is a combined work of both human and nature. The study of cultural landscape in a region is helpful to discover the historical changes and human factors in the region. With the development and maturity of digital technology, there are many kinds of research ways, such as UAV, satellite remote sensing, etc. Firstly, this paper collects and understands the domestic and foreign research examples, then analyzes the application advantages of UAV in cultural landscape research, and then takes Guling, Fujian Province as an example to carry out the landscape culture research using UAV technology, and finally summarizes that UAV technology can provide reliable data sources for Cultural Landscape Archaeology, solve the accessibility problem in Cultural Landscape Archaeology Research, and provide more perspectives for desktop work.